2022
DOI: 10.1007/s10664-022-10130-9
|View full text |Cite
|
Sign up to set email alerts
|

Quality gatekeepers: investigating the effects of code review bots on pull request activities

Abstract: Software bots have been facilitating several development activities in Open Source Software (OSS) projects, including code review. However, these bots may bring unexpected impacts to group dynamics, as frequently occurs with new technology adoption. Understanding and anticipating such effects is important for planning and management. To analyze these effects, we investigate how several activity indicators change after the adoption of a code review bot. We employed a regression discontinuity design on 1,194 sof… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 72 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…Wessel et al [62] studied the impact of adopting code review bots and found that it accelerates the increasing trend in the number of merged PRs, accelerates the decreasing trend in the number of closed PRs, decreases the number of comments in all PRs, increases the resolution time of merged PRs, and reverses the increasing trend in the resolution time of closed PRs. In another study, Wessel et al [65] investigated the impact of adopting GitHub Actions and found that it decreases the number of both merged PRs and closed PRs, increases the number of discussion comments in merged PRs, decreases the number of discussion comments in closed PRs, increases the resolution time of merged PRs, and decreases the resolution time of closed PRs. However, our study focuses on investigating the impact of adopting Stale bot to better understand its helpfulness for pull-based development.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Wessel et al [62] studied the impact of adopting code review bots and found that it accelerates the increasing trend in the number of merged PRs, accelerates the decreasing trend in the number of closed PRs, decreases the number of comments in all PRs, increases the resolution time of merged PRs, and reverses the increasing trend in the resolution time of closed PRs. In another study, Wessel et al [65] investigated the impact of adopting GitHub Actions and found that it decreases the number of both merged PRs and closed PRs, increases the number of discussion comments in merged PRs, decreases the number of discussion comments in closed PRs, increases the resolution time of merged PRs, and decreases the resolution time of closed PRs. However, our study focuses on investigating the impact of adopting Stale bot to better understand its helpfulness for pull-based development.…”
Section: Related Workmentioning
confidence: 99%
“…To investigate the impact of adopting Stale bot, we first need to quantify the performance of the pull-based development workflow in the studied projects. For this purpose, we consult similar studies that investigated the effect of an intervention on the pull-based development of opensource projects [62,65]. As shown in Table 3, we measure 13 performance indicators covering six dimensions: (1) resolved PRs, (2) review latency, (3) resolution time, (4) review discussion, (5) PR updates, and (6) contributor retention.…”
Section: Approachmentioning
confidence: 99%
See 3 more Smart Citations